2017
DOI: 10.1136/annrheumdis-2016-210322
|View full text |Cite
|
Sign up to set email alerts
|

Tofacitinib in patients with ankylosing spondylitis: a phase II, 16-week, randomised, placebo-controlled, dose-ranging study

Abstract: ObjectivesTo compare efficacy and safety of various doses of tofacitinib, an oral Janus kinase inhibitor, with placebo in patients with active ankylosing spondylitis (AS, radiographic axial spondyloarthritis).MethodsIn this 16-week (12-week treatment, 4-week washout), phase II, multicentre, dose-ranging trial, adult patients with active AS were randomised (N=51, 52, 52, 52, respectively) to placebo or tofacitinib 2, 5 or 10 mg twice daily. The primary efficacy endpoint was Assessment of SpondyloArthritis Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
192
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 321 publications
(212 citation statements)
references
References 41 publications
(34 reference statements)
7
192
0
13
Order By: Relevance
“…77,78 Tofacitinib is now approved for this indication ( Table 2). Other forms of arthritis in which jakinibs are being studied include ankylosing spondylitis 79 and juvenile idiopathic arthritis (NCT01500551, NCT02592434).…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…77,78 Tofacitinib is now approved for this indication ( Table 2). Other forms of arthritis in which jakinibs are being studied include ankylosing spondylitis 79 and juvenile idiopathic arthritis (NCT01500551, NCT02592434).…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…A phase II study of tofacitinib showed benefit in both clinical and imaging outcomes of axial disease over 12 weeks (20 In adults with active AS despite treatment with NSAIDs, we strongly recommend treatment with TNFi over no treatment with TNFi (PICO 6).…”
Section: Very Low 70mentioning
confidence: 99%
“…in patients with moderate to severe chronic plaque psoriasis has been demonstrated in global phase 3 trials 20-23 of up to 56 weeks' duration, and in a long-term extension (LTE) study with efficacy end-points reported through 24 months and safety reported over 33 months of exposure. 23 The efficacy and safety of tofacitinib has also been studied in several other immune-mediated inflammatory diseases, including rheumatoid arthritis, [24][25][26][27][28][29] psoriatic arthritis (NCT01877668, NCT01882439, NCT01976364), ankylosing spondylitis, 30 Crohn's disease 31 (NCT01393626, NCT01393899, NCT01470599) and ulcerative colitis. 32,33 The phase 3 OPT Pivotal 1 study in psoriasis included sites in Japan; here, we report the results of post-hoc analyses of data for the Japanese patients enrolled in OPT Pivotal 1.…”
Section: Introductionmentioning
confidence: 99%